Silly Putty: Mobilization of the Known Across Technology-Enhanced Learning Spaces - Wong, Melanie M. (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
In technology-enhanced classrooms, due to the affordances of technologies, English Language Learners (ELLs) are moving between learning spaces; boundaries are never clear. Questions arise with regards to how students’ non-sanctioned experiences might mediate classroom learning. Using a multiliteracies (New London Group, 2000) and learning by design (Cope & Kalantzis, 2015) theoretical lens, this ethnographic case study explores the technology-enhanced learning experiences of Grade 6 ELLs. Data including field observations, artifacts, and interviews were analyzed using thematic analysis (Saldaña, 2016). Findings of this study indicate that ELL students were engaged in learning experiences that encouraged them to mobilize their known (knowledge) across learning spaces.